CD70 is a therapeutic target upregulated in EMT-associated EGFR tyrosine kinase inhibitor resistance - Nilsson, Monique B.; Yang, Yan; Heeke, Simon; Patel, Sonia A.; Poteete, Alissa; Udagawa, Hibiki; Elamin, Yasir Y.; Moran, Cesar A.; Kashima, Yukie; Arumugam, Thiruvengadam; Yu, Xiaoxing; Ren, Xiaoyang; et al. (Cancer cell, 2023)
Effective therapeutic strategies are needed for non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations that acquire resistance to EGFR tyrosine kinase inhibitors (TKIs) mediated by epithelial-to-mesenchymal transition (EMT). We investigate cell surface proteins that could be targeted by antibody-based or adoptive cell therapy approaches and identify CD70 as being highly upregulated in EMT-associated resistance. Moreover, CD70 upregulation is an early event in the evolution of resistance and occurs in drug-tolerant persister cells (DTPCs). CD70 promotes cell survival and invasiveness, and stimulation of CD70 triggers signal transduction pathways known to be re-activated with acquired TKI resistance. Anti-CD70 antibody drug conjugates (ADCs) and CD70-targeting chimeric antigen receptor (CAR) T cell and CAR NK cells show potent activity against EGFR TKI-resistant cells and DTPCs. These results identify CD70 as a therapeutic target for EGFR mutant tumors with acquired EGFR TKI resistance that merits clinical investigation. [Display omitted] •CD70 is upregulated on EGFR mutant NSCLC cells that have undergone EMT•In EGFR inhibitor-resistant cells, CD70 regulates cell survival and invasiveness•CD70 upregulation occurs in drug-tolerant persister cells (DTPCs)•Drug-resistant CD70+ tumors can be targeted with CD70-ADCs, CAR Ts, and NK-CARs Nilsson et al. show that CD70 is highly upregulated in non-small cell lung cancer (NSCLC) tumors with acquired EGFR tyrosine kinase inhibitor (TKI) resistance that occurs independent of MET or secondary EGFR mutations. Anti-CD70 antibody drug conjugates and CD70-targeting CAR T and CAR NK cells have activity against resistant cells and drug-tolerant persister cells.